Evaluation of Sustainable Tourism of Pacal Reservoir Based on Environment, Economic and Social Perspectives in Bojonegoro Regency - Yuli Anita; Bambang Semedi; Ratno Bagus Edy Wibowo; Bunga Hidayati (Postgraduate, University of Mataram, 2025)
Pacal Reservoir has a function to irrigate agriculture in the Bojonegoro Regency area. Pacal Reservoir also has beautiful natural potential so that it is used as a mainstay tourism object of Bojonegoro Regency. The existence of the reservoir that has been for 90 years, makes the pacal reservoir experience several problems. The purpose of this study is to analyze pacal reservoir tourism into sustainable tourism. The method used is qualitative descriptive. The analysis used is a SWOT analysis. The results of the SWOT analysis are at the coordinate point (0.37; 0.28) where the coordinate point is in quadrant I. So that pacal reservoir tourism has opportunities and strengths, namely in that position is the most advantageous situation. Based on this study, it can be concluded that the results of the SWOT matrix produce several strategies when viewed in terms of environmental, social and economic tourism of the pacal reservoir. The result of the SWOT coordinate point is in quadrant I. Position in quadrant I means having opportunity and strength. The strategy that must be taken in conditions like this is to support an aggressive growth-oriented strategy by utilizing existing opportunities and strengths possessed.